2012
DOI: 10.3136/fstr.18.383
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic Effects of Adlay Protein in Type 2 Diabetic db/db Mice

Abstract: We examined the effects of adlay protein concentrates (AP) on lipid metabolism and on in vivo oxidative stress in type 2 diabetic db/db mice. Mice were fed an AIN-93G diet containing either adlay grains (AG) or AP for 21 days. Plasma parameters, such as total cholesterol, arteriosclerotic index and thiobarbituric acid reactive substances (TBARS) concentration in the diabetic AP-fed group were lower than those in the diabetic control (AIN-93G) group. Concentrations of hepatic parameters, such as total cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Adlay has been reported to have anti-inflammatory and antioxidant properties and has been used in the treatment of edema, rheumatism, and neuralgia [13,14,15,16]. Many components of adlay have been identified as having biological functions; adlay-related proteins can improve type II diabetes [17] and the oil fraction of adlay seeds has displayed an effect on the reduction of blood lipids in hyperlipidemic rats [18].…”
Section: Introductionmentioning
confidence: 99%
“…Adlay has been reported to have anti-inflammatory and antioxidant properties and has been used in the treatment of edema, rheumatism, and neuralgia [13,14,15,16]. Many components of adlay have been identified as having biological functions; adlay-related proteins can improve type II diabetes [17] and the oil fraction of adlay seeds has displayed an effect on the reduction of blood lipids in hyperlipidemic rats [18].…”
Section: Introductionmentioning
confidence: 99%
“…Prolamins accounted for nearly 60% of adlay seed storage proteins [6]. Adlay protein and peptides have various pharmacological actions, including CVD and hypertension [7,8]. Previous research has proven that bioactive peptides released by enzymatic digestion were effective components of adlay for hypertension and ACE inhibiting [9].…”
Section: Introductionmentioning
confidence: 99%
“…Coix seeds are rich in protein and amino acids and have dual functions of being medicine and food. However, only a few studies have reported the functions of peptides from Coix [ 6 ]. Therefore, it is necessary to further characterize the peptides from Coix seeds.…”
Section: Introductionmentioning
confidence: 99%